Nanotechnology to Overcome World’s Most Critical Health Issues: Liposomes and beyond—a Themed Issue Dedicated to Professor Yechezkel Barenholz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focuses on a variety of nanotechnology platforms, including liposomes, which are used for the delivery of therapeutics and vaccines in order to solve the world’s most critical health issues and to support environmental sustainability.